Sociocultural perceptions of walkability in Mexican American neighborhoods: Implications for policy and practice - Ingram, Maia (J Transp Health, 2017)
Walking is the most fundamental form of active travel, as well as the most popular form of physical activity. The built and social environment, however, may not adequately support active living, especially in low-income communities. While improving the walking infrastructure is essential, assumptions regarding perceptions of walkability based on a standardized norm may fail to address preferences within specific populations. Particularly in low-income and ethnically diverse urban environments, it is not clear whether objective or perceived measures provide the best assessment of an environments’ conduciveness to walkability. This qualitative study of five Mexican American neighborhoods used walk-and-talk focus groups (n=20) and intercept surveys (n=108) to investigate residents’ perceptions of their walking environments. Respondents differentiated between physical and social attributes in assessing neighborhood walkability. Physical attributes, such as lack of infrastructure, maintenance and traffic, were more salient to residents when describing what discouraged them from walking. Perceptions of the social environment appeared to be of greater significance than the physical environment in encouraging individuals to walk. While respondents were concerned about personal safety, the overall sociability of the neighborhood, nearby family, familiarity between neighbors, and a sense of social activity all contributed to a positive assessment of walkability and expressed desire to walk, Findings revealed complex interactions between characteristics of the social, built, natural, and policy environments. The emphasis on sociocultural influences on perceptions of walkability underscores the importance of engaging neighborhoods in conversations about their walking environments to reveal strategies that better serve the needs of residents.